Right ventricular infarction: diagnostic accuracy of electrocardiographic right chest leads V3R to V7R investigated prospectively in 43 consecutive fatal cases from a coronary care unit. Issue 6 (June 1989) - Andersen, H R; Falk, E; Nielsen, D
Abstract : The accuracy of ST elevation greater than or equal to 1 mm in right chest leads V3R to V7R in the diagnosis of right ventricular infarction was investigated in a clinical and necropsy study of 43 consecutive patients who died in a coronary care unit. Thirty six patients had left ventricular myocardial infarction and in 27 the right ventricle was also affected. Seven patients had normal hearts. The specificity and positive predictive value of ST elevation in V3R were 81% and 77%, respectively. These increased to 100% when combined with ST elevation in one or more leads V4R-V7R. The diagnostic accuracy was poor for anterior infarcts (sensitivity less than or equal to 27%), but high for inferior/posterior infarcts (sensitivity greater than or equal to 64%) in which the specificity and positive predictive value reached 100% in V6R and V7R. Inferior/posterior infarction affecting the right ventricle can be diagnosed reliably by examination of electrocardiograms from right chest leads V6R and V7R.